Strategi Pembangunan Pedesaan melalui Implementasi Desa Sejahtera Mandiri (DSM) di Malang dan Mojokerto - suprapto, Suprapto; Santosa, Santosa (MAJAPAHIT POLICY, 2024)
Independent Prosperous Village (DSM) aims to achieve community welfare. Efforts made are reducing the number of poor people and providing skills/soft skills. DSM seeks to resolve the number of poor people and welfare efforts in 4 villages (Gajahrejo, Sidodadi, Pamotan, and Lebakjabung). This study aims to focus on the planning, implementation and targets of the DSM program. The approach in this study is participatory policy research. The data sources in this study are LP2M UM, TKSK, Village Apparatus, some program recipients, Village Youth, and Pokdarwis/LMDH. Data collection was carried out through observation, interviews, focus group discussions (FGD), and documentation studies. The results of this study indicate that the DSM programs that have been implemented are the Uninhabitable House (RTLH) program, Joint Business Groups (KUBE), and tourism development. With program targets in accordance with the recipient criteria according to the data on People with Social Welfare Problems (PMKS). 30 RTLH have been built and 2 (two) KUBEs have been formed per village. So from the DSM target, there are still 2 (two) programs implemented from 9 (nine) program achievements. In the field of tourism development, it has been running according to the established tourism concept.